Oropharyngeal shedding of herpesviruses before and after BNT162b2 mRNA vaccination against COVID-19. Issue 40 (24th September 2021) - Brosh-Nissimov, Tal; Sorek, Nadav; Yeshayahu, Michal; Zherebovich, Irena; Elmaliach, Maria; Cahan, Amos; Amit, Sharon; Rotlevi, Erela
Highlights: BNT162b2 might be associated with increased incidence of Bell's palsy, herpes simplex and zoster. Oropharyngeal samples before and 1 week after vaccination were tested for 7 herpesviruses. No increase in herpesviruses shedding was seen after BNT162b2 vaccination. Abstract: Introduction: Concerns were raised over an increase in Bell's palsy, herpes simplex and herpes zoster after BNT162b2 vaccination, all are manifestations of herpesviruses reactivation. As herpesviruses commonly reactivate in the oropharynx, we have hypothesized that oropharyngeal shedding of herpesviruses will increase after vaccination. Methods: Immune-competent Adults, excluding those using topical steroids or manifesting symptomatic herpesvirus infection, were sampled before BNT162b2 vaccination and one week after. Herpesviruses 1–7 shedding was tested with a multiplexed PCR. Results: In 103 paired samples the prevalence of herpesviruses was similar before and after vaccination: HSV1, 3.9% vs. 5.8% (p = 0.75); HSV2, 0% vs. 1% (p = not applicable, NA); VZV, 0% vs. 0% (p = NA); EBV, 14.6% vs. 17.5% (p = 0.63); CMV, 0% vs. 0% (p = NA); HHV6, 4.9% vs. 7.8% (p = 0.55); HHV7, 71.8% vs. 72.8% (p = 1); any herpesvirus, 73.8% vs. 74.8% (p = 1). Discussion: We did not find evidence for increased oropharyngeal reactivation of herpesviruses one week after BNT162b2.